Correlates of Young Men's Intention to Discuss Birth Control with Female Partners. Issue 1 (1st November 2016) - Masters, N. Tatiana; Morrison, Diane M.; Querna, Katherine; Casey, Erin A.; Beadnell, Blair
Abstract: CONTEXT: Heterosexually active men who wish to prevent conception, but are not willing to use condoms consistently, need to discuss birth control with female partners. Improving the understanding of correlates of men's intention to have such discussions is one step toward supporting this health‐facilitating behavior. METHODS: A sample of 372 heterosexually active men aged 18–25 were recruited and surveyed online between December 2010 and June 2011. Men answered questions on attitudes toward, norms regarding and self‐efficacy about discussing birth control, and about endorsement of two sexual scripts. Multiple regression analyses tested these measures' associations with intention to discuss birth control, controlling for age and relationship status. RESULTS: Attitudes, norms and self‐efficacy were each positively associated with men's intention to discuss birth control, accounting for 34% of variance. The more strongly men endorsed a traditional masculinity sexual script, the less likely they were to intend to discuss birth control (coefficient, –0.2). Endorsement of an alternative, gender‐equitable "sex‐positive woman" script, which emphasizes sexual pleasure and emotional connection as goals for both partners, had no association with intention. CONCLUSION: Strategies that merit further exploration as potential supports for men's intention to discuss birth control include improving men's self‐efficacy and positive attitudes and norms pertaining to such discussions, and reducing belief in traditionally masculine sexual scripts or transforming them to include discussing birth control. Future research should work both experimentally and longitudinally to document each element of the process that ends with men's full participation in effective contraceptive use.